Enhanced anti-stocks luminescence in LaNbO4:Ln3+ (Ln3+ = Yb3+, Er3+/Ho3+/Tm3+) with abundant color. Issue 27 (16th March 2017) - Huang, Huining; Zhou, Haifeng; Zhou, Juan; Wang, Tao; Huang, Dapeng; Wu, Yaqiang; Sun, Leilei; Zhou, Guangjun; Zhan, Jie; Hu, Jifan
Abstract : A 980 nm laser was employed to excite Yb 3+ ions to achieve the 2F7/2 → 2F5/2 transition, and the LNO:Yb 3+, Er 3+ /Ho 3+ /Tm 3+ samples exhibited intense green, yellowish-green and blue emission, respectively. Abstract : Lanthanide ion doped up-conversion luminescent (UCL) materials, which have the ability to convert near-infrared longer wavelength excitation light into shorter wavelength visible light, have recently drawn much attention. Now, a series of Ln 3+ (Yb 3+, Er 3+ /Ho 3+ /Tm 3+ ) ions doped LaNbO4 (LNO) materials were prepared through a two-step route, including a facile sol–gel process and subsequent combustion. In our work, thermogravimetric and differential thermal analysis (TG-DTA), X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), up-conversion luminescence (UCL), energy level diagram, luminescent lifetimes and corresponding CIE were utilized to characterize the properties. A 980 nm laser was employed to excite Yb 3+ ions to achieve the 2 F7/2 → 2 F5/2 transition, and the LNO:Yb 3+, Er 3+ /Ho 3+ /Tm 3+ samples exhibited intense green, yellowish-green and blue emission, respectively. Luminescent spectra at different powers demonstrated the two-photon absorption process; meanwhile, the corresponding energy transfer mechanisms from Yb 3+ to Ln 3+ and the emissions of Ln 3+ under 980 nm laser excitation were described via an energy level diagram. Moreover, multicolor UCL emissions, the optimal intensities and corresponding mechanism were systematically explored via a suite of concentration spectra of different Ln 3+ ions. At last, the decay lifetimes based on the concentration variation of Yb 3+ ion demonstrated that the lifetimes are heavily influenced by Yb 3+ ion.